ChemInform Abstract: From Iridium and Platinum to Copper and Carbon: New Avenues for More Sustainability in Organic Light‐Emitting Diodes. Issue 23 (June 2015) - Volz, D.; Wallesch, M.; Flechon, C.; Danz, M.; Verma, A.; Navarro, J. M.; Zink, D. M.; Braese, S.; Baumann, T.
Abstract Review: 181 refs.